The market reaction to Arthur Andersen's role in the Enron scandal: Loss of reputation or confounding effects? - Nelson, Karen K.; Price, Richard A.; Rountree, Brian R. (Journal of Accounting and Economics, 2008)
This paper tests the hypothesis that negative client stock returns following the revelation that Enron documents had been shredded are attributable to confounding effects as opposed to a loss of Andersen's reputation. We find that a sharp decline in oil prices along with differences in the industry composition of the Andersen and Big 4 client portfolios combine to produce significantly more negative returns for Andersen clients relative to Big 4 clients, and for Andersen's Houston office clients relative to its clients in other locations. The market reaction to two other Enron-related events also offers little support for a reputation effect.